2011
DOI: 10.1103/physreva.83.033411
|View full text |Cite
|
Sign up to set email alerts
|

Photofragmentation of tetrahydrofuran molecules in the vacuum-ultraviolet region via superexcited states studied by fluorescence spectroscopy

Abstract: Photofragmentation of tetrahydrofuran molecules in the vacuum-ultraviolet region, producing excited atomic and molecular fragments, has been studied over the energy range 14-68 eV using photon-induced fluorescence spectroscopy. Excited hydrogen atoms H(n), n = 3-11, have been detected by observation of the H α to H ı lines of the Balmer series. The diatomic CH(A 2 ), CH(B 2 − ) and C 2 (d 3 g ) fragments, which are excited to low vibrational and high rotational levels are identified by their A 2 → X 2 r , B 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…The dispersed fluorescence spectra of isoxazole were measured using an experimental set-up that was described in detail in [8]. Briefly, a monochromatized photon beam provided by the beamline crossed the effusive beam of the sample molecules emanating from a hypodermic needle.…”
Section: Methodsmentioning
confidence: 99%
“…The dispersed fluorescence spectra of isoxazole were measured using an experimental set-up that was described in detail in [8]. Briefly, a monochromatized photon beam provided by the beamline crossed the effusive beam of the sample molecules emanating from a hypodermic needle.…”
Section: Methodsmentioning
confidence: 99%
“…It is visible from Figure 5 that values of this ratio obtained for protons are much higher than that for the C + and O + cations. The enhancement of hydrogen peaks in the present experiment cannot be explained by fragmentation of the target molecule itself, because on one hand the formation of the CH radicals is minor as compared to other impact systems [14,15,[25][26][27][28][29][30] and on the other hand the production of the excited hydrogen atoms from neutralized protons, due to electron capture mechanism, is energetically the most favored channel [15].…”
Section: Collisional Processesmentioning
confidence: 99%
“…Also fluorescence spectrum measured in the studies of electron impact excitation of furan [25] presents pronounced intensity of the diatomic CH fragments formed in the A 2 Δ, B 2 Σ − and even C 2 Σ − electronic states and the C 2 fragments in the d 3 Π g excited state. Present results of fragmentation of furan molecule may also be compared to the photon [26][27][28], cation [15] and electron [29,30] impact fragmentation of other five-and six-membered heterocyclic molecules. Again in contrast to present measurement all these studies demonstrated major fragmentation of the target molecules into several different atomic and diatomic fragments.…”
Section: Hementioning
confidence: 99%
“…Motohashi et al observed in their electron impact excitation experiments with methane an exponent of 4.5 ± 0.2 for the Balmer series [20] in agreement with [32]. In contrast, the exponential factors of the Balmer hydrogen series for dissociation of larger molecules like furan, tetrahydrofuran and isoxacole [34][35][36] yielded values much closer to the theoretical value (between 3.2 and 3.74). The dependence of the Balmer line intensities on n as obtained in the present experiment is presented in figure 4.…”
Section: Balmer Series -H(n 3→2)mentioning
confidence: 77%